Analisis Peningkatan Pendapatan Daerah melalui Kebijakan Pengembangan Ecowisata dan Wisata Halal Kabupaten Langkat - Harjo Santoso; Nuri Aslami; Rahmat Daim Harahap (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Tourism is one sector that can help increase the income of a region. Many regions depend on their income from the tourism sector. Tourism has several types where tourism can be in the form of natural tourism, building tourism, or artificial tourism. In developing tourism in Indonesia, the government has a policy offer in the form of managing ecotourism and halal tourism. Ecotourism is a type of tourism object that has the aim of protecting the environment and sustainability, while halal tourism is the concept of fulfilling the halal aspects of a tourist attraction in the form of lodging, culinary, and other supporting aspects. This paper aims to analyze the increase in Langkat district's original income through tourism management with aspects of ecotourism and halal tourism. This paper has a qualitative approach with the interview research method where the researcher conducted interviews with several people related to tourism in Langkat district, this paper has the result that tourism does not have a significant influence on regional income if it is not managed properly with clear directions and objectives.